The Fourth Congress of Muslim Librarians and Information Scientists - Yahya Monastra (International Institute of Islamic Thought, 1996)
This conference was a rare occasion for Muslim scientists and scholars to assemble and discuss the challenges facing the ummah. Inaugurated by Farooq Ahmad Khan Leghari, the president of Pakistan, the conference consisted of fifty papers presented in eight inaugural and plenary sessions. The issues discussed were of both theoretical and practical import. The theoretical papers focused on such questions as the nature and significance of science, the concept of Islamic science, and Islamic epistemology. According to Ziauddin Sardar, who gave the public lecture "Islamic Science: The Way Ahead," science is a highly complex and multilayered activity, for no single and simple description of science can reveal its true nature; no romantic ideal can describe its real character; no sweeping generalization can uncover its authentic dimensions. In particular, both the extreme positions of scientific fundamentalism and fundamentalist relativism are untenable. He stated that science has been under the influence of the dominant western paradigm and that the selection of research priorities is of fundamental importance in scientific research, for "often it is the source of funding that defines what problem is to be investigated.'' Some 80 percent of American research is funded by the "military-industrial complex" and is geared to producing military and industrial equipment. As modem science is based on western values and the priority given to scientific investigation is determined by western requirements, science must be indigenized. Muslim countries have a valuable and untapped reservoir of knowledge and experience. so such an indigenization would be like a rediscovery. But this process, Sardar maintains, "must begin by a rejection of both the axioms about nature, universe, time, and humanity as well a5 the goals and direction of western science and the methodology which hac; made meaningless reductionism, objectification of nature, and torture of animals its basic approach." By Islamic science he means a scientific activity pursued within the framework of a set of fundamental Islamic concepts. Sardar supports the concepts, identified by Muslim scientists at the Stockholm Seminar (1981), that should shape the science policies of Muslim societies: tawhid (unity), khilafah (trusteeship), 'ibadah (worship) ...